The development of the thermal tourism market in Poland // Rozwój rynku turystyki termalnej w Polsce - Dryglas, Diana; Hadzik, Andrzej (Geotourism/Geoturystyka, 2017)
Thermal tourism in Poland has been gaining in popularity for over a decade now. This refers to both the supply and demand sides of the market. Therefore, the aim of this paper is to describe the current situation, as well as the prospects of formation and development of the thermal tourism market in Poland. To do that, a number of research methods had to be employed, including a critical analysis of literature on the subject, statistical data analysis, a case study (the example of Poland), methods of observation and inference by deduction within the scope of the research question asked. Based on the results of secondary research and an in-depth review of literature on the subject, one can conclude that Polish thermal tourism market is not growing steadily. On the one hand, there is considerable consumers’ interest in using geothermal pools, while on the other the geothermal potential for medical and recreational purposes remains unexploited. // Od kilkunastu lat turystyka termalna w Polsce cieszy się coraz większą popularnością. Stąd też celem artykułu jest próba nakreślenia obecnej sytuacji oraz perspektyw powstania i rozwoju rynku turystyki termalnej w Polsce. Realizacja celu pracy wymagała zastosowania kilku metod badawczych, takich jak krytyczna analiza literatury przedmiotu, analiza danych statystycznych, studium przypadku (przykład Polski), metody obserwacji, oraz wnioskowania przez dedukcję w zakresie postawionego pytania badawczego. Na podstawie wyników badań wtórnych i dogłębnego przeglądu literatury przedmiotu można stwierdzić, że rynek turystyki termalnej rozwija się nierównomiernie. Bowiem z jednej strony mamy do czynienia z dużym zainteresowaniem konsumentów korzystaniem z basenów geotermalnych z drugiej zaś obserwuje się niewykorzystany potencjał geotermalny mogący służyć do celów leczniczych i rekreacyjnych.